Green new deal and the question of environmental and social justice - Christoph Herman (International Labour Organization (ILO), 2015)
The financial and economic crisis was preceded by an energy, food and climate crisis. Until 2008, prices for oil, food and various minerals were increasing due to accelerating scarcity in peak capitalism. With the outbreak of the financial turbulences, the environmental problems shifted somewhat to the background, but various academics and policy makers emphasized the multiple nature of the current crisis. A number or organizations, subsequently, called for the adoption of a Green New Deal to tackle ecological and economic problems. The idea was that investments in energy efficiency and renewable energy production would improve ecological sustainability, while at the same time generating growth and creating jobs. Some organizations saw the adoption of a Green New Deal as a first step in a transition towards a green economy. This paper critically examines the content of various Green New Deal proposals and analyzes the nature of a green economy with respect to their impact on equality. The major finding is that current concepts to not address the unequal distribution of environmental and economic assets and even tend to fortify gender inequality.
Keywords: 330; sustainable development; economic recovery; employment creation; green jobs; environmental protection; equal rights